Analyzing Neovascular Glaucoma and Angle-Closure Glaucoma - Wilda Najmi Hentihu; Nanda Lessi Hafni Eka Putri (International Journal Labs, 2023)
Neovascular glaucoma (NVG) is a secondary glaucoma that is generally associated with a poor visual prognosis. The development of new blood vessels above the iris and iridocorneal angle can block the outflow of aqueous humor and cause an increase in intraocular pressure. This study intends to analyze neovascular glaucoma and angle-closure glaucoma. This research is a case study conducted in a regional hospital in West Java. Researchers make direct observations in the field and collect data from observations and documentation. Researchers found that if acute angle-closure glaucoma is not detected and treated in its early stages, it can lead to temporary vision loss or blindness. There is loss of peripheral vision, followed by loss of central vision. There can be a significant increase in IOP in patients with peripheral patent iridotomy and flat front chambers of the eye. This condition is called malignant glaucoma. This condition is difficult to treat and progressively leads to blindness.